Notes to the current checklist of Tardigrada - Degma, Peter; Guidetti, Roberto (Zootaxa, 2007)
Corrections and additions to the recently published checklist of Tardigrada taxa (Guidetti & Bertolani 2005) are defined and described until the acceptance of this article. Two new synonyms are stated here: Hypsibius iharosi Bartoš, 1941 syn. nov. and Isohypsibius gibbus (Marcus, 1928) syn. nov.